2008
DOI: 10.1507/endocrj.k07e-110
|View full text |Cite
|
Sign up to set email alerts
|

ChREBP: A Glucose-activated Transcription Factor Involved in the Development of Metabolic Syndrome

Abstract: Abstract. Excess carbohydrate intake leads to fat accumulation and insulin resistance. Glucose and insulin coordinately regulate de novo lipogenesis from glucose in the liver, and insulin activates several transcription factors including SREBP1c and LXR, while those activated by glucose remain unknown. Recently, a carbohydrate response element binding protein (ChREBP), which binds to the carbohydrate response element (ChoRE) in the promoter of rat liver type pyruvate kinase (LPK), has been identified. The targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 49 publications
4
121
1
4
Order By: Relevance
“…Recently, it has been reported that glucose activates ChREBP, a carbohydrate responsive element binding protein identified as a key regulator of glucose and lipid metabolism. 33 Specifically, a diet rich in glucose has been shown to activate hepatic ChREBP in animal models leading to an increased expression of enzymes involved in the formation of triglycerides. 34,35 In this study, we confirmed these results and showed an elevated mRNA expression of ChREBP associated with increased levels of FAS and triglycerides in the liver of mice fed a 30% glucose solution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that glucose activates ChREBP, a carbohydrate responsive element binding protein identified as a key regulator of glucose and lipid metabolism. 33 Specifically, a diet rich in glucose has been shown to activate hepatic ChREBP in animal models leading to an increased expression of enzymes involved in the formation of triglycerides. 34,35 In this study, we confirmed these results and showed an elevated mRNA expression of ChREBP associated with increased levels of FAS and triglycerides in the liver of mice fed a 30% glucose solution.…”
Section: Discussionmentioning
confidence: 99%
“…PKLR is a rate-limiting enzyme in the glycolytic pathway and plays an important role in the regulation of glycolysis and lipogenesis [6,7]. TXNIP has an important role in glucose toxicity in pancreatic β cells [26].…”
Section: Dg Can Induce Pklr and Txnip Mrna Expression In A Time-and mentioning
confidence: 99%
“…Carbohydrate response element-binding protein (ChREBP) as well as SREBP-1c plays a pivotal role in the generation of hepatic lipogenesis in response to changes in glucose in the liver [66][67][68]. We have demonstrated that ChREBP gene expression is positively regulated by thyroid hormone [69].…”
Section: Carbohydrate Response Element-binding Protein (Chrebp)mentioning
confidence: 99%